(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Breeding biology of the Red-whiskered Bulbul, Pycnonotus jocosus (Linnaeus, 1758) in Madhupur National Park (MNP), Bangladesh, was carried out from January to June in 2009. The breeding season lasted from February to May. Both the parents built a hollow cup-shaped nest, the weight, length, and depth of which were respectively, 9.9-12 g (10.98±0.78 g), 8-10 cm (8.98±0.67 cm), and 4.1-5 cm (4.62±0.312 cm). The outer and inner diameter of the nest opening was 8-9.7 cm (8.92±0.54 cm) and 6-7.5 cm (6.72±0.49 cm), respectively. The height of the nest from the ground ranged from 0.6-2.1 m (1.41±0.55 m). They took 14-16 days (15±0.85 days) in nest building and laid 2-4 (2.74±0.81) whitish with brown blotched eggs. The egg size was 2.10×1.45 cm. The hatchlings hatched out after 12-15 days (13.14±1.17 days) of incubation period and fledged between 13-18 days (14.85±1.77 days) after hatching. The breeding success was 81.82% in relation to nestlings hatched and 51.92% in relation to eggs laid. Infertility (47.36%) was the leading cause of egg loss and stolen (66.67%) for nestlings. J. Asiat. Soc. Bangladesh, Sci. 46(2): 179-189, December 2020